Ethical concerns and suggested mitigation strategies related to student-facing learning analytics dashboards – a narrative literature review - Havinen, Laura; Dang, Duong; Rousi, Rebekah (RWTH Aachen, 2026)
Student-facing learning analytics dashboards (LADs) enable students to access and view learning analytics (LA) data. While having access to LA data and the related recommendations offer benefits for the students, there are several ethical concerns involved. This narrative literature review describes the ethical concerns related to student-facing LADs and lists suggested mitigations to minimize the ethical risks. Five ethical concerns were identified: threat to privacy, lack of transparency and fairness, potential misuse of power relations, prediction sideeffects, and restriction on autonomy. Mitigations to minimize ethical problems were related to providing students with transparent information about LA in a clear, comprehensible way, complying with ethical guidelines and regulations, and implementing tools in the LADs that make it possible to manage the data as well as personalize the output. As a result of the study, a model of ethical concerns in student-facing LADs as well as principal mitigation strategies for these concerns are proposed.
Keywords: learning analytics; dashboards; ethics; transparency; fi=Tietojärjestelmätiede|en=Information Systems Science|; fi=Tietojärjestelmätiede|en=Information Systems Science|; fi=Viestintätieteet|en=Communication Studies|